Programma: 2 februari: Club Locale; 14 februari: Sleeze Beez; 17 februari: Jim Rose Circus Side Show; 15 februari: Living Colour (1993)
Programma: 2 februari: Club Locale; 14 februari: Sleeze Beez; 17 februari: Jim Rose Circus Side Show; 15 februari: Living Colour.